Potential of LiNO3/Al2O3 Catalyst for Heterogeneous Transesterification of Palm Oil to Biodiesel - Istadi Istadi; Bambang Pramudono; Suherman Suherman; Slamet Priyanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2010)
Production of biodiesel through transesterification process using heterogenous catalysts in order to avoid the saponification problem was studied. In this process, palm oil reacted with methanol to form a mixture of glycerol and biodiese over a solid basic catalyst. One type of the catalysts used in this research is basic catalyst of LiNO3/Al2O3. The parameters studied in this research are concentration of LiNO3 loading on Al2O3 and effect of different reaction time. The products was analyzed using Gas Chromatography to determine composition and yield of resulted methyl esters as well as conversion of palm oil to biodiesel. The major products in this transesterification reaction were biodiesel and glycerol. It can be concluded that the 20 wt% LiNO3/Al2O3 catalyst is potential for producing biodiesel from palm oil over transesterification reaction. Advantages of the usage of this catalyst is that the soap formation was not observed in this research. © 2010 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)